COMBINED EFFECT OF PNF STRETCHING WITH CHEST MOBILITY EXERCISES ON CHEST EXPANSION AND PULMONARY FUNCTIONS FOR ELDERLY (International Journal of Physiotherapy, 2015)
Background: PNF stretching and chest mobility exercises found to be effective in elder patients, however the combined effectiveness of these techniques were unknown. The purpose of this study is to find the effect of Hold-relax PNF stretching technique for pectoralis muscle combined with chest mobility exercises on improvement of chest expansion and pulmonary function for elderly subjects.Method: An Experimental study design, 30 subjects with age group above 60 years were randomized 15 subjects each into Study and Control group. Control group received Supervised Active Assisted Exercise Program while Study group received Hold-relax PNF Stretching for pectoralis muscle, Chest Mobility Exercises Program and supervised Active Assisted Exercise Program for a period of one week. Outcome measures such as chest expansion at axilla and xiphisternum and pulmonary function test such as FEV1, FVC and FEV1/FVC were measured before and after one week of treatment.Results: Analysis using paired ‘t’ test within the group found that there is no statistically significant difference within control group where as there is a statistical significant difference within study group. Comparative analysis of pre-intervention means shown that there is no statistically significant difference between the groups. Comparative analysis of post-intervention means shown that there is a statistically significant difference in means of Chest expansion, FEV1/FVC and there is no statistical significant difference in FEV1 and FVC between study and control groups.Conclusion: It is concluded that one week of combined Hold-relax PNF stretching for pectoralis muscle with chest mobility exercises shown significant improvement in chest expansion and pulmonary function test such as forced expiratory volume and forced vital capacity than only active assisted exercise program for elderly subjects.